(Eyes of the Dream) as a First Meta-Narration in the Kurdish Short Story in Bahdinan - Haji, Nafisa; Brindar, Nazdar (Humanities Journal of University of Zakho, 2021)
Meta-Narration is a narrative phenomenon that dates back to the postmodern period. It is known that the emergence and development of the Kurdish short story in Bahdinan was delayed, so it is possible that the short story, which is an example of this study that entitled (Eyes of the Dream) by (Kareem Jamil Bayani) in (1987) to be the first meta- narration in the Kurdish short story in Bahdinan, and this is what this study attempted to prove. The appearance of the first Kurdish short story with the features of a tale in Bahdinan dates back to (1960). In the eighties of the twentieth century the features of the Kurdish short story were realistic. However, its real development was in the nineties, because after the emergence of modernity groups, it began to experiment and employ new technologies. Because the short story (Eyes of the Dream) dates back to the eighties and it seems that it has been written in the meta-narrative techniques, in this study it has been presented as an example of meta-narrative in the Kurdish short story in Bahdinan, and this was the first issue that theresearch studied. Thus, the issue raised in this paper is that meta-narrative techniques have been extensively employed in the text, so the hypothesis here is that this text could be a first example of meta-narrative techniqe in the Kurdish short story. Moreover, the study attempts to clarify the phenomenon of meta-narration, its history, terms and concept. Furtheremore, it identified the meta-narration’s techniques that have been employed in the short story (Eyes of the Dream). In order for the paper to achieve its objectives, in general it depends on the narratology, and the characteristics and foundations of the phenomenon of meta-narration that have been identyfied by critics.